2015
DOI: 10.1016/j.juro.2014.07.098
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis of Transperineal Template Saturation Prostate Biopsy Versus Magnetic Resonance Imaging Targeted Biopsy with Magnetic Resonance Imaging-Ultrasound Fusion Guidance

Abstract: Compared to systematic, transperineal biopsy as a reference test, magnetic resonance imaging targeted biopsy alone detected as many Gleason score 7 or greater tumors while simultaneously mitigating the detection of lower grade disease. The gold standard for cancer detection in primary biopsy is a combination of systematic and targeted cores.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
118
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 189 publications
(148 citation statements)
references
References 30 publications
13
118
0
3
Order By: Relevance
“…More biopsies were found positive in the fused group and more malignant tissue was found per biopsy, 40 even accomplishing results similar to transperineal 3-D prostate mapping biopsy. 41 Our hypothesis is that integrating OCT in the combined results of MRI/TRUS fusion will further improve the diagnostic accuracy. Moreover, results will become objective and real time.…”
Section: Discussionmentioning
confidence: 99%
“…More biopsies were found positive in the fused group and more malignant tissue was found per biopsy, 40 even accomplishing results similar to transperineal 3-D prostate mapping biopsy. 41 Our hypothesis is that integrating OCT in the combined results of MRI/TRUS fusion will further improve the diagnostic accuracy. Moreover, results will become objective and real time.…”
Section: Discussionmentioning
confidence: 99%
“…This subgroup of low-risk PCa seems to be a tough challenge for diagnostic tools. Radtke et al [3] reported 12% missed Gleason score 6 tumors, when only mp-MRI PIRADS 3-5 lesions [17] are targeted for biopsy. This limitation seems to be the same for elastography, in which in case of a ‘negative elastogram' around 20% harbor cancerous tissue (most of them Gleason score <7) in the systematic biopsy (unpublished data of the Hamburg group).…”
Section: Discussionmentioning
confidence: 99%
“…He was not able to show a significant correlation between tumor volume by HS and radical prostatectomy (RP) specimen in a cohort of 148 patients. In the mean time, other diagnostic tools like elastography, multiparametric magnetic-resonance imaging (mp-MRI) and MRI/transrectal ultrasound (TRUS) fusion biopsies showed promising results in PCa detection [3,4,5,6,7,8]. This study aims at validating the previous results of HS on the gold standard of RP specimen and put them into the context of other available diagnostic modalities for PCa detection.…”
Section: Introductionmentioning
confidence: 91%
“…Consequently, the significantly lower performance of the systematic biopsy should have been anticipated. A more extended biopsy approach was followed by Radtke et al [3]; in their study a transperineal template saturation biopsy (median 24 cores) was combined with MRI-ultrasound fusion guided targeted biopsy and lead to detection of 11 (7%) additional cases of csPCa (a total of 153 patients with a PIRADS score >=3). A PIRADS score of <3 on mpMRI was present in 141 patients (48%) with 17 (12%) of them being diagnosed with a csPCa detected by systematic biopsy.…”
Section: Cancer 2016 Mar 15;122(6):884-92mentioning
confidence: 99%